Reestablishment of Occlusal Vertical Dimension in Complete Denture Wearing in Two Stages - Mendoza Marin, Danny Omar [UNESP]; Perin Leite, Andressa Rosa [UNESP]; Martins De Oliveira, Norberto Junior [UNESP]; Antonio Compagnoni, Marco [UNESP]; Carolina Pero, Ana [UNESP]; Arioli Filho, Joao Neudenir [UNESP] (Hindawi Ltd, 2015)
The assessment and reestablishment of the occlusal vertical dimension (OVD) are considered important factors in the treatment of complete denture wearers. The long-time use of a complete denture can result in jaw displacement due to abrasion of the artificial teeth and residual ridge resorption, causing esthetic complications. Most patients with old dentures and incorrect OVD accept reestablishment of the OVD with new complete dentures, even if they were used to their old dentures. The present clinical report describes a method of gradual reestablishment of OVD using a diagnostic acrylic splint on artificial teeth in old complete dentures before the manufacture of new complete dentures. Clinical Significance. The use of a reversible treatment for reestablishment of the OVD in old complete dentures with a diagnostic occlusal acrylic splint allows for the reestablishment of the intermaxillary relationship, providing physiological conditions of masticatory performance associated with the recovery of facial esthetics in edentulous patients.